A study on hazard of EMF caused by cellular phone and tablet on children awareness in Malaysia / Amirul Asyraf Norizan - Norizan, Amirul Asyraf (Faculty of Art and Design, 2017)
EMF (Electromagnetic Field) is a invisible form of hazard energy which can cause damage to children health such as their brain. This is because the anatomy of children is basically not as tough as adults but it is fragile. Nowadays, many parents in Malaysia doesn’t seem to realize or fully aware that cellular phone and tablet can cause brain damage to our children. As a matter a fact, parents use cellular phone or tablet as tools for distracting their children while they are busy with something else. However, there are still a room for doing the right thing which is encourage and always remind the parents of the danger or the hazard of EMF. Cellular phone or tablet radiation that produces by those devices everyday can be harmful to their children. The Intention of this study is to create awareness for the parents to remind that cellular phone and tablet it is not tools that can help them distract their child while they are busy. Questionnaire was used as tools for collecting data from 50 respondents which is by using Typeform.com. In this study, the researcher has used one method and that is quantitative. After finding result, an advertising and a campaign will be creating. The significance is to educate Malaysian parents on the danger of EMF for their children.